EVALUATE THE EFFICACY OF ASHTAVARGASIDDHA BASTI AND UPANAHA SWEDA IN THE MANAGEMENT OF SANDHIGATAVATA - Pareek, Tribhuvan; Belavadi, S. N.; Purad, U. V. (International Journal of Ayurveda and Pharma Research, 2015)
Sandhigatavata is the most common form of joint disorder amongst the elderly and obese persons. It is a major cause of morbidity and chronic disability as well as burden on healthcare resources especially for the elderly. This disease keeps an insidious attack, which runs for many years causing the loss of function as well as deformity of the joints, especially weight bearing joints like knee joint. The study was done in two groups, Group A and Group B each group having 15 patients. Patients of Group A received the treatment modalities Ashtavargasiddha Niruhabasti for 8 days. Where, Patients of Group B received Ashtavargasiddha Niruhabasti for 8 days followed by Upanaha Sweda for next 8 days. Subjective parameters were Sandhi Ruk (Pain), Sandhi Graha (Stiffness), Sparshaakshamatva (Tenderness), Sandhi Shotha (Swelling), Sandhi Atopa (Crepitation) and objective parameters were WOMAC, Range of movements, Walking time. According to the statistical analysis Parameters Sandhi Ruk, Walking time better responded in group A compared to group B, Whereas Parameters Sandhi Graha, Sparshaakshamatva (Tenderness), Sandhi Shotha (Swelling), Sandhi Atopa (Crepitation) and objective parameters as WOMAC, Range of movements responded equally in both groups, But more in Group B by comparing their t-values.